2011
DOI: 10.1063/1.3657779
|View full text |Cite
|
Sign up to set email alerts
|

Doping of GaN1−xAsx with high As content

Abstract: Recent work has shown that GaN1−xAsx can be grown across the entire composition range by low temperature molecular beam epitaxy with intermediate compositions being amorphous, but control of the electrical properties through doping is critical for functionalizing this material. Here we report the bipolar doping of GaN1−xAsx with high As content to conductivities above 4 S/cm at room temperature using Mg or Te. The carrier type was confirmed by thermopower measurements. Doping requires an increase in Ga flux du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Furthermore, both p-type and n-type doping of a partially amorphous GaN1-xAsx (x~0.55-0.65) have been demonstrated [80,81]. We observed that the room temperature p-type conductivity of GaN1-xAsx increased monotonically with increasing of Mg content, up to a maximum value of about 55 S/cm for 8 atomic % Mg content [80]. We have found that achieving of the p-type doping of GaN1-xAsx, requires growth under Ga-rich conditions.…”
Section: Lt-mbe Grown Gan1-xasx Over the Entire Composition Rangementioning
confidence: 99%
“…Furthermore, both p-type and n-type doping of a partially amorphous GaN1-xAsx (x~0.55-0.65) have been demonstrated [80,81]. We observed that the room temperature p-type conductivity of GaN1-xAsx increased monotonically with increasing of Mg content, up to a maximum value of about 55 S/cm for 8 atomic % Mg content [80]. We have found that achieving of the p-type doping of GaN1-xAsx, requires growth under Ga-rich conditions.…”
Section: Lt-mbe Grown Gan1-xasx Over the Entire Composition Rangementioning
confidence: 99%
“…These semiconductors were grown using highly non-equilibrium low-temperature molecular beam epitaxy (LT-MBE) at temperatures between 200-300 o C. Recently we have already reported that p doping of GaN 1-x As x using Mg is possible [10]. In this paper we focus on the relation between the microstructure and conductivity of these samples.…”
mentioning
confidence: 99%
“…The active N flux with the total N beam equivalent pressure (BEP) ~5.5x10 -6 Torr and 2.2x10 -7 were used in all growth. The details of this growth were reported earlier [1,2,10]. For p-doping Mg concentration was controlled by Mg BEP of 6.6x10 -9 Torr.…”
mentioning
confidence: 99%
“…A hole concentration of 8.5×10 19 cm -3 is achieved which allows a specific contact resistance of 1.3×10 -4 Ω-cm 2 . An increased gallium beam equivalent pressure during growth allows reduced resistivity but can result in the formation of a polycrystalline structure.…”
mentioning
confidence: 99%
“…1 A hole concentration up to 1×10 20 cm -3 was achieved and the electrical properties of the free carriers were studied. 2 The high hole concentration can be used to improve the performance of electronic devices such as PN diodes, pGaN gated HFETs and JFETs. However, reports on the characteristics of the material in electronic devices is still lacking.…”
mentioning
confidence: 99%